PEMBUATAN BRIKET ARANG LIMBAH KAYU JABON DAN LIMBAH SERAT KELAPA SAWIT DENGAN PEREKAT DAMAR - Haryati Haryati; Rudianda Sulaeman; Yossi Oktorini (Fakultas Pertanian, Universitas Riau, 2017)
This research is aimed to get alternative fuel in the form of charcoal briquettes from raw material of wood waste of jabon and waste of palm fiber with adhesive resin and know characteristics of charcoal briquette from mixing waste wood of jabon and waste of palm fiber. The method used in this research is Completely Randomized Design (RAL), consisting of 5 treatments and 3 times replications.The results showed that biomass waste from wood jabon and palm fiber waste can be used as alternative fuel in the form of charcoal briquettes with adhesive resin.Characteristics of wood charcoal briquette of jabon wood and palm fiber waste have fulfilled the criteria of SNI 01-6235-2000 with the average value of water content of wood charcoal briquettes 2.33%, average of the calorific value of wood charcoal briquettes 6525,48 kal / gr ,While from burning process of P1 briquettes wood charcoal jabon takes the longest time compared with other treatment briquettes whose value of 0.256 gr / min. In this research it is found that the best charcoal briquettes are found on charcoal P1 briquettes with 100% composition of wood charcoal Jabon.The P1 briquette has the lowest water content, the highest calorific value and the longest burn time